Christology as a Function of Epistemology: A Bibliographic Study in the Theology of Paul Tillich - Johnson, Wendell G. (Journal of religious and theological information, 2018)
Paul Tillich is widely regarded as one of the theological giants of twentieth-century theology, and yet, according to Russell Re Manning, remains perhaps the most neglected great theologian of recent times (Re Manning, 2009). This study, based on Tillich's three-volume Systematic Theology (1967) describes Tillich's epistemology and discusses its effect upon his Christology, specifically with a view towards the concept "the uniqueness of Christ." The article concludes with bibliographic annotations on Tillich's life.